The Influence of Saturated Fats, Cholesterol, Corn Oil and Linseed Oil on Experimental Venous Thrombosis in Rats - Nordøy, Arne (Thrombosis and Haemostasis, 1965)
1. The effect of different fat diets on the incidence of thrombus formation has been examined in rats using a standardized damage of the jugular vein.2. An increased incidence of thrombosis was observed in animals given a diet containing 10% hydrogenated coconut fat and 1 per cent cholesterol as the only fat ingredients. The addition of corn oil to the diet did not influence the hyperthrombotic state whereas addition of linseed oil significantly reduced the incidence of thrombosis.3. An accelerated recalcification time, cephalin time and thromboplastin time, as well as an increase in the levels of fibrinogen, factor V, VII and VIII was observed in animals on the saturated fat diet. This hypercoagulable condition was not influenced by addition either of corn oil or of linseed oil to the diet.4. A moderate hyperlipemia was present in the animals on a saturated fat and cholesterol diet. This was reduced but not normalized when corn oil or linseed oil was added to the diet.5. The present study indicates a correlation between a hyperthrombotic, a hypercoagulable and a hyperlipemic condition. However, the antithrombotic effect of linseed oil can neither be correlated with changes in the coagulation mechanism nor with changes in the main blood lipid fractions.